ANALYSIS OF THE EFFECT OF PROFITABILITY, LEVERAGE, AND LIQUIDITY ON FIRM VALUE WITH SUSTAINABILITY REPORT DISCLOSURE AS MODERATING VARIABLE IN SERVICE COMPANIES LISTED ON INDONESIA STOCK EXCHANGE (IDX) IN 2013 – 2017 - Sylvia, Sylvia (Asosiasi Dosen Akuntansi Indonesia, 2021)
This research aims to analyze the effects of profitability, leverage and liquidity towards firm value as well as the effects of sustainability report disclosure as moderating variable on Service companies that are listed in Indonesian Stock Exchange from 2013 – 2017. Populations of this research are all service companies that are listed in Indonesian Stock Exchange during 2013 until 2017. Samples of this research are 9 service companies that are listed in Indonesia Stock Exchange during 2013 – 2017. This research used Multiple Regression Analysis for the hypothesis 1 – 4 and Absolut Residual Analysis to analyze moderating variable that are in hypothesis 5 – 7. The results of this research show that, (1) Profitability has a positive and significant effect on firm value, (2) Leverage has a negative and significant effect on firm value, (3) Liquidity has a negative and significant effect on firm value, (4) Profitability, Leverage, and Liquidity are significant on firm value, (5) Sustainability Report Disclosure indeed is a moderating variable that affects the relationship between profitability and firm value, (6) Sustainability Report Disclosure is not a moderating variable that affects the relationship between leverage and firm value, and (7) Sustainability Report Disclosure indeed is a moderating variable that affects the relationship between liquidity and firm value.